Structure of Metacommunicative Comment and Folk Conceptions of Communication (based on Russian- and Belarusian-language internet forums of Belarus) - Bobko, Tatyana (Respectus Philologicus, 2017)
The article discusses the factors of speaker’s choice of additional metacommunication moves in non-institutional internet communication. The study is based on Russian- and Belarusian-language internet forums of Belarus, which allows to observe directly the metacommunicative reflection of speakers. The research has a comparative aspect and focuses on similarities and differences in verbalised metacommunication conceptions of Russian and Belarusian-speaking Belarusians, caused by the attitude to the language of communication: the language situation of Belarus, in which formally equilateral languages have in fact unequal conditions of functioning, actualises the symbolic use of the Belarusian language. It has been established that the choice of additional metacommunication moves with a particular function in Russian and Belarusian-speaking internet communication is determined by such factors as speakers’ representations about the communication norms and focus on certain communication aspects; for the Belarusian-language internet dialogue a special relation to the language, conditioned by its ethno-consolidating and symbolic functions, becomes relevant.